Study of Histological changes in the kidney of female white rat treated with Cefixime Drug - Abbas, Zainab Abdul Kareem (Technium: Romanian Journal of Applied Sciences and Technology, 2025)
This study was prepared to discuss the histological changes caused by Cefixime treatment on female rats. 24 animals were selected with weights about 170-220 grams & These animals were in good health, were subjected For good ventilation and suitable laboratory conditions, the animals were divided into (3) groups. The group (1) Was isolated with Distill Water as a control group & the other groups were given using Cefixime as an overdose for 10 days, and 5 days respectively every 12 hours daily. The results appeared that tissue damage occurred in the kidney tissues as: Renal tubular Dissection, Necrosis of the renal tubules, proliferative glomerulonephritis, hemorrhage within the kidney tissue.